2007
DOI: 10.1002/anie.200702185
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Reactions of α‐Sulfonyl Carbanions of Trifluoromethyl Sulfones

Abstract: Making a resolution: The catalytic enantioselective reaction of lithiated benzyl trifluoromethyl sulfone with aldehydes delivers products with excellent diastereoselectivity as well as high enantioselectivity. Fluorination of the sulfone with N‐fluorobenzensulfonimide in the presence of a stoichiometric amount of bis(oxazoline)s resulted in extremely high enantioselectivity (up to 99 % ee, see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The authors showed that the driving force for the resolution was formation of homochiral dimers or oligomers 12b. Since the N- methyl analog of 5 is a homochiral dimer13 and the N- ethyl analog is a mixture of aggregates,14 a similar effect may be operative here (although we observe no precipitation).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…The authors showed that the driving force for the resolution was formation of homochiral dimers or oligomers 12b. Since the N- methyl analog of 5 is a homochiral dimer13 and the N- ethyl analog is a mixture of aggregates,14 a similar effect may be operative here (although we observe no precipitation).…”
supporting
confidence: 56%
“…To our knowledge, there is only one previous report of a DTR using substoichiometric quantities of chiral ligand 12. The authors showed that the driving force for the resolution was formation of homochiral dimers or oligomers 12b.…”
mentioning
confidence: 99%
“…However as Toru has shown, 6 irreversible population of a homochiral aggregate from a racemic monomer or a heterochiral aggregate by catalytic dynamic resolution is possible. In the case of the piperidines under study in this work, there is some evidence of differences in solution structure between racemic and enantioenriched 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Toru reported a catalytic dynamic resolution (CDR, Scheme 2), which is driven by the well-known phenomenon of crystallization-induced asymmetric transformation. 6 In the Toru example, the resolution is accomplished by dynamic resolution of planar-chiral organolithium enantiomers by the bisoxazoline ligand, followed by precipitation of homochiral aggregates (an asymmetric transformation of the second kind). Addition of aldehyde caused dissolution of the precipitate, and after quenching with Me 3 SiCl and acidic workup, the product was isolated in good yield, with excellent diastereoselectivity and enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The use of asymmetricp rotocols [19] (likelyt ob ec hallenging given the inherent difficulties of asymmetric a-functionalisation of S=Ob onds) [20,21] in this process has, to date, provedn onproductive, delivering allylated products in variable yields and with no discernible enantioselectivity.T his matter is currently the focus of intense interestino ur laboratories.…”
mentioning
confidence: 99%